ENHANCING METHANE PRODUCTION FROM RICE STRAW CO-DIGESTED WITH BUFFALO DUNG BY OPTIMIZING EFFECT OF SUBSTRATE RATIO, ALKALINE DOZE AND PARTICLE SIZE - A. R. Sahito; R. B. Mahar (Journal of Animal and Plant Sciences, 2014)
The purpose of this study was to enhance the methane generation from the rice straw by anaerobically co-digestion with the buffalo dung. The study was carried out into three phases and it includes determination of ratio of rice straw and buffalo dung, specific mass of sodium bicarbonate (NaHCO3) as buffer and alkaline pretreatment agent and appropriate size of the rice straw particle size that yields maximum methane. The higher generation of methane from anaerobic co-digestion of rice straw and buffalo dung could be achieved by taking the ratio of rice straw and buffalo dung as 3:7 on the basis of volatile solids, the specific mass of NaHCO3 of 0.5 g/gVS and the rice straw particle size of 2 mm. Considering the above parameters, methane generation was obtained about 184 NmL/gVS at anaerobic biodegradability of about 48%. By using particle size of 4mm, methane generation was obtained about 172 NmL/gVS. However, because of about double energy consumption to produce rice straw of particle size of 2 mm than to the particle size of 4 mm, thus on the basis of energy consumption later one is suggested as appropriate particle size.
Keywords: methane; buffalo dung; rice straw; specific mass of sodium bicarbonate; particle size